IoT and Raspberry Pi application in the food industry: a systematic review (Research, Society and Development, 2022)
The Industry 4.0 technologies are in ascension in the worldwide market, in Brazil still needs to be explored. It was made a Systematic Review to measure the application of IoT in the food industry. Some platforms were used to select works, applying the string “IoT AND Raspberry Pi AND Cheese”. It was possible to evidence the majority of IoT applications in the food industry, focus on the control of temperature, humidity, color, traceability of productive chain, and enlargement of sustainability in the food industry. The most difficulties faced in the conventional application of IoT are related to the high cost of proprietary arquitectures, qualified manpower and obstacles of data security implementation. There are alternatives that aim to reduce the costs of implementation, like the utilization of Raspberry Pi. The food industry presents potential application of technologies that aim for the quality of products, being an excellent opportunity.